1906. Hospitalization Rates Among Persons With HIV Who Gained Medicaid or Private Insurance in 2014. (26th November 2018) - Chow, Jeremy; Nijhawan, Ank; Raifman, Julia; Gebo, Kelly; Moore, Richard; Berry, Stephen; ,
Abstract: Background: The Ryan White Program (RWP), which provides safety net outpatient healthcare coverage to thousands of low-income persons with HIV (PWH), does not pay for inpatient care. Many PWH who relied on RWP transitioned to either Medicaid or private insurance (private) with the Affordable Care Act in 2014. It is unknown whether such transitions affected hospitalization rates. Methods: We included patients from three HIV Research Network sites (two in Medicaid expansion states, one in a nonexpansion state) who relied solely on RWP in 2013. Patients either stayed in RWP through 2015, or changed to Medicaid or private in 2014. 2015 hospitalization rate ratios were modeled using negative binomial regression, adjusting for demographics, CD4 count, HIV viral load (VL), clinic site, and number of 2013 hospitalizations. Results: Our sample of 1, 634 patients was 73% male, 46% Black, 36% Hispanic; median age was 45 years (IQR 37, 52) and median CD4 count 526 cells/μL (356, 716); 85% had a VL ≤400 copies/mL. Ninety-five patients were hospitalized in 2015. Unadjusted hospitalization rates (per 100 person years) were 8.4, 21.3, and 7.4 in 2013 and 6.3, 20.2, and 3.7 in 2015 for those who remained in RWP, switched to Medicaid, or switched to private, respectively. Switching to Medicaid or private was not associated with 2015 hospitalization rates (IRR 1.26 (95% CI 0.71–2.23) and 0.48 (0.18–1.28), table). Older age, CD4 <200, VL >400, and number of 2013 hospitalizations were associated with higher rates. Conclusion: Among PWH relying on RWP in 2013, changing to either Medicaid or private insurance was not associated with a change in hospitalization rate. Among PWH, gaining inpatient coverage does not appear to increase inpatient utilization. Disclosures: A. Nijhawan, Gilead: Consultant, Research support.